Exploring Language Disorders: Assessment, Intervention,and Strategies for Supporting Individuals (Journal of Asian Development Studies, 2024)
Language disorders are considered a substantial neurodevelopmental disability, within which 7-10% of children of the global population are affected by different forms of language disorders.These disorders are defined by impairment of language understanding and production, showinglifelong impacts on cognition, learning, communication and social interaction. These questionsinclude: what are the causes of language disorders, how is language disorder diagnosed, and whatare the best practices when treating a person with language disorder? This research uses a mixedmethod research design based on theoretical foundations such as the biopsychosocial model, theNeurocognitive Developmental Model by Paula Raja and the Social Interactionism model by UzerKaya. A bibliography review was conducted, supplemented by using standardized language tests,neuropsychological examinations, and case reports to study the frequency and cognitive effects oflinguistic impairments. These research findings show that language disorders are directly relatedto severe attention and memory problems, and the structural differences in the brain areidentifiable. Furthermore, these disorders come with social and emotional impacts since thepatient suffers from anxiety, depression, or poor academic performance. Dynamic assessment andcontext-based student and context-specific early intervention can effectively reduce these impacts.Applying evidence-based learning across individual learning underscores the need to incorporatecognitive and social factors while teaching language disorders, which is key to the study. Thisstudy supports the intervention of multiple disciplines and early detection to improve languageand quality of life in affected people.